Facilitating childbirth choice for positive postnatal mental health well-being among women: a Namibian case study - Mlambo, S.; Amukugo, H. J. (Frontiers in Global Women's Health, 2024)
Childbirth affects women in a myriad of ways including feelings of tiredness, being overwhelmed, stressed, and having baby blues, and if not attended to, this can lead to postpartum depression, which is a mental condition that can have disastrous effects. Childbirth affects the mental and physical status of a woman and having supportive midwives who guide women by giving adequate information is an issue of critical concern for a positive birth experience. Some women may experience worry and anxiety during labour and childbirth, which may be exacerbated by bias and a lack of childbirth choice facilitation during pregnancy. A negative childbirth experience may lead to negative psychological distress and postpartum depression, which will interfere with the bond between the mother, baby, and family. Midwives, thus, need to understand the emotional aspects that are attached to childbirth and be able to facilitate and support the emotional as well as the psychosocial needs of women under their care. However, there is a dearth of empirical evidence within the Namibian context that can provide direction and context-specific solutions to the present challenge. The current study followed a qualitative research design with an exploratory approach with one-on-one interviews with 10 midwives who were purposively selected. Two themes emerged with subthemes namely; barriers in the facilitation of childbirth choices (shortages of staff, the timing of information, information sharing) and a lack of provision for childbirth choice (Provision of rights of women regarding choice Lack of woman-centred care Enforcement of protocols and guidelines Cultural influences on childbirth types). In conclusion, midwives as primary caregivers of women actively need to provide unbiased childbirth information to achieve positive postpartum health. Initiating childbirth choices early in pregnancy gives women the time to weigh options and clearing of any misconceptions relating to childbirth types as well as reducing anxiety and fear of birth, which could lead to postpartum depression and by extension, the mental well-being of the women. Facilitating the childbirth choices is critical in positive birth experiences and the management of childbirth as well as crafting guidelines and policy formulation that ensure a mentally healthy woman, baby and society.